Plant Composition and Feed Value of First Cut Permanent Meadows - Aldo Dal Prà; Roberto Davolio; Alessandra Immovilli; Andrea Burato; Domenico Ronga (Agronomy, 2023)
Permanent grasslands represent the main terrestrial ecosystem and serve as an important global reservoir of biodiversity, providing a wide range of benefits to humans and ecosystems. The effects of environment on permanent meadows (in our survey, they were centuries-old meadows that had not been plowed, mowed, or fertilized with manure) production have been adequately investigated in literature. However, plant species composition impact on potential feed value of first cut has still to be understood, in particular regarding different agronomic management. Our field trial was carried out in five farms, in a territory involved in the value chain of the Parmigiano Reggiano PDO (Val d’Enza, Northern Italy), over a two-year period (2017–2018). Differences in botanical composition, biomass, and Pastoral Value index (PV), which synthesizes grassland yield and nutritional parameters, were investigated in depth. The herbage dry matter (DM) yield was affected by year, farm, and their interaction factors. Its highest value across the two years was recorded in farm 5 (11.7 tons of DM ha−1), which applied the highest rate of nitrogen fertilization. The botanical composition of the first cut has favored the presence of both Poaceae and ‘other species’ (each one around 40 plants per transect) compared to Fabaceae (seven plants per transect). However, higher numbers of Fabaceae plants (13 and 10) plausibly determined increases in PV in farms 3 and 5 (56.4 and 58.7, respectively). Although differences were observed among the most important nutritional parameters of grassland (crude protein, digestible and undigested neutral detergent fiber contents), suitable net energy for lactation (NEL) values for feeding lactating cows were always recorded during the two years of survey. The present study provides a contribution of knowledge on how the botanical composition of permanent meadows may affect their potential nutritive value as fresh herbage for feeding dairy cows. Considering these results, the agronomic management should seek a level of plant biodiversity that at the same time might guarantee satisfactory yield and feed value, also in a context of climate change.